2018
DOI: 10.1002/jpln.201700554
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia losses from urea applied to winter wheat over four consecutive years and potential mitigation by urease inhibitors

Abstract: Urea is not only the most important mineral nitrogen (N) fertilizer worldwide, but it is also the mineral N fertilizer with one of the highest potential for ammonia (NH3) losses. The European emission inventory guidebook estimates an average loss of 16% of the applied urea as NH3. For mitigating NH3 losses from urea, the best option would be to immediately incorporate the fertilizer. However, the addition of a urease inhibitor (UI) represents a potent alternative. In a multi‐year experiment from 2002 to 2005, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
0
0
Order By: Relevance
“…A multi-year, multi-site NH 3 volatilization study in corn conducted in Tennessee showed a positive correlation with total NH 3 volatilization loss and mean temperature in the 20 d after application (Liu et al, 2019). Similar conclusions were found in a multi-year volatilization study in winter wheat in Germany, with greater losses during measurement campaigns with higher temperatures (Schraml, Weber, Heil, Gutser, & Schmidhalter, 2018).…”
Section: Ammonia Volatilization Losses: 3-year Averagesupporting
confidence: 76%
“…A multi-year, multi-site NH 3 volatilization study in corn conducted in Tennessee showed a positive correlation with total NH 3 volatilization loss and mean temperature in the 20 d after application (Liu et al, 2019). Similar conclusions were found in a multi-year volatilization study in winter wheat in Germany, with greater losses during measurement campaigns with higher temperatures (Schraml, Weber, Heil, Gutser, & Schmidhalter, 2018).…”
Section: Ammonia Volatilization Losses: 3-year Averagesupporting
confidence: 76%
“…However, the major reasons leading to low NH3 emission in southern Germany may be due to low pH values of the investigated soils together with increased cation exchange capacity, and low temperature prevailing in April and frequent precipitation events after N application. However, the 7.7% of the applied urea N from NH3-N losses was higher than the 0.1-2.7% in southern Germany reported by Schraml et al [6]. This discrepancy may be attributable to the higher pH at the experimental site of this study (pH = 6.7).…”
Section: Cumulative Nh 3 Emissions During Growth Periods Under Differ...contrasting
confidence: 77%
“…Furthermore, our long-term studies on N 2 O emissions have shown that averaged N 2 O emissions over many years were consistent (back to the 1990s, e.g., [23][24][25][26]). In particular, NH 3 emission from U from 2001 to 2010 were much less variable with years and were limited to a small range of 1-3.4% of urea-N applied during the growing seasons of winter wheat [6,[25][26][27][28][29]. A simulation study on modeling NH 3 emissions across Germany [30] showed that NH 3 emissions (% urea N applied) were in a range of 0-10% in strong contrast to the averaged 24% for European arable soils assumed by EMEP/EEA [31].…”
Section: Experimental Site and Designmentioning
confidence: 99%
See 2 more Smart Citations